Hybrid h-BN/ZnO Nanolubricant Additives in 5W-30 Engine Oil for Enhanced Tribological Performance of Magnesium Alloys - Gurgenc, Turan (Mdpi, 2025)
Magnesium alloys are widely used in automotive and aerospace applications due to their light weight but suffer from poor tribological performance. This study investigates the effects of base oil (SAE 5W-30) with 100% hBN, 100% ZnO, and various ratios of hBN/ZnO hybrid nanoparticles on the tribological performance of AZ91D magnesium alloy. Pin-on-disk tribometer tests were conducted on AZ91D magnesium alloy under loads of 10-60 N and a sliding distance of 1000 m. Dry sliding produced the highest coefficient of friction (COF, similar to 0.30) and the greatest wear. Base oil lubrication reduced COF to similar to 0.14 and improved wear resistance by more than 50%. The 100% hBN nanolubricant provided the lowest wear and a COF of similar to 0.114, while the 75hBN/25ZnO hybrid achieved the lowest COF (similar to 0.110) with wear values close to hBN. Surface analyses confirmed that hBN formed a lamellar tribofilm that minimized metal-to-metal contact, and ZnO contributed to the formation of load-bearing oxide layers that enhanced surface stability. Overall, the results demonstrate that hBN and ZnO, in single or hybrid form, can significantly reduce friction and wear, showing strong potential for applications in automotive, aerospace, defense, and industrial systems.
Keywords: magnesium alloy; nanomaterial; nanolubrication; friction; wear